2018
DOI: 10.21577/1984-6835.20180097
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Antimicrobial Activity of Soil Fungus Aspergillus sp. FRIZ12

Abstract: Constituintes Químicos e Atividade Antimicrobiana do Fungo de Solo Aspergillus sp. FRIZ12 Resumo: O presente trabalho relata o isolamento de nove compostos da biomassa do fungo de solo Aspergillus sp. FRIZ12. Os compostos 2-benzil-4H-piran-4-ona (1), flavasperona (2), 5-(hidroximetil) furfural (3), uridina (4), ergosterol (5), peróxido de ergosterol (6), cerivisterol (7), estigmasterol (8) e sitosterol (9) foram isolados por métodos cromatográficos, e as estruturas foram identificadas por RMN, EM e comparação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Our result revealed that the extract and the compounds exert a significant anti-inflammatory effect and the most potent one is compound 2 as previously reported that butenolides can exhibit anti-inflammatory activity (Qia et al 2018 ). Moreover, it was reported that the extract obtained from A. terreus showed an antimicrobial activity against different strains of microorganisms (Pinheiro et al 2018 ). The biological activity of the extract may be due to the synergistic activity of the different compounds present in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…Our result revealed that the extract and the compounds exert a significant anti-inflammatory effect and the most potent one is compound 2 as previously reported that butenolides can exhibit anti-inflammatory activity (Qia et al 2018 ). Moreover, it was reported that the extract obtained from A. terreus showed an antimicrobial activity against different strains of microorganisms (Pinheiro et al 2018 ). The biological activity of the extract may be due to the synergistic activity of the different compounds present in the extract.…”
Section: Discussionmentioning
confidence: 99%